KONSEP PENDIDIKAN ISLAM PADA MASA KHULAFAUR ROSYIDIN - Muthoharoh, Miftakhul; Aisyah, Siti (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
Religious education for Muslims is an Islamic education that comes from the Al-Qur'an and As Sunnah. This article discusses the dynamics of change and development of Islamic Education in the period after the death of the Prophet Muhammad shallall?hu'alaihi wa sallam, especially the development of Islamic Education during the Rashidun Khulafaur era. Described how the education system that was applied to each caliph and the various situations behind the education system that was applied at that time. This research applies library research with the documentation method. The results of this study indicate that the pattern of education during the time of Caliph Abu Bakar radh?yall?hu‘anhu was generally the same as the pattern of education during the time of the Prophet Muhammad shallall?hu 'alaihi wa sallam. The development of Islam very rapidly occurred during the Caliph Umar bin Khatab radh?yall?hu 'anhu which was continued by the Caliph Uthman bin Affan radh?yall?hu 'anhu. However, there have been a number of fundamental changes that have taken place, particularly in terms of the policies and methods of education that have been implemented.